The TGFβ-signaling pathway and colorectal cancer: associations between dysregulated genes and miRNAs - Andrew J. Pellatt (Journal of Translational Medicine, 2018)
Abstract Background The TGFβ-signaling pathway plays an important role in the pathogenesis of colorectal cancer (CRC). Loss of function of several genes within this pathway, such as bone morphogenetic proteins (BMPs) have been seen as key events in CRC progression. Methods In this study we comprehensively evaluate differential gene expression (RNASeq) of 81 genes in the TGFβ-signaling pathway and evaluate how dysregulated genes are associated with miRNA expression (Agilent Human miRNA Microarray V19.0). We utilize paired carcinoma and normal tissue from 217 CRC cases. We evaluate the associations between differentially expressed genes and miRNAs and sex, age, disease stage, and survival months. Results Thirteen genes were significantly downregulated and 14 were significantly upregulated after considering fold change (FC) of > 1.50 or < 0.67 and multiple comparison adjustment. Bone morphogenetic protein genes BMP5, BMP6, and BMP2 and growth differentiation factor GDF7 were downregulated. BMP4, BMP7, INHBA (Inhibin beta A), TGFBR1, TGFB2, TGIF1, TGIF2, and TFDP1 were upregulated. In general, genes with the greatest dysregulation, such as BMP5 (FC 0.17, BMP6 (FC 0.25), BMP2 (FC 0.32), CDKN2B (FC 0.32), MYC (FC 3.70), BMP7 (FC 4.17), and INHBA (FC 9.34) showed dysregulation in the majority of the population (84.3, 77.4, 81.1, 80.2, 82.0, 51.2, and 75.1% respectively). Four genes, TGFBR2, ID4, ID1, and PITX2, were un-associated or slightly upregulated in microsatellite-stable (MSS) tumors while downregulated in microsatellite-unstable (MSI) tumors. Eight dysregulated genes were associated with miRNA differential expression. E2F5 and THBS1 were associated with one or two miRNAs; RBL1, TGFBR1, TGIF2, and INHBA were associated with seven or more miRNAs with multiple seed-region matches. Evaluation of the joint effects of mRNA:miRNA identified interactions that were stronger in more advanced disease stages and varied by survival months. Conclusion These data support an interaction between miRNAs and genes in the TGFβ-signaling pathway in association with CRC risk. These interactions are associated with unique clinical characteristics that may provide targets for further investigations.